Natural and semi-synthetic insecticides protect onion from wireworms Agriotes spp. larvae (wireworm) damage - Prijović, Mirjana; Dervišević, Marina; Drobnjaković, Tanja; Stojanović, Luka; Miladinović, Vladimir; Ugrinović, Milan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2025)
Wireworms, the larval stage of click beetles (Elateridae: Agriotes spp.), pose asignificant threat to global agriculture, particularly to root vegetables, such as onion.Their subterranean lifestyle, as well as the withdrawal of some traditional syntheticinsecticides, make them challenging to control. Therefore, this research aimed tocompare the effects of natural, semi-synthetic and synthetic insecticides in controllingwireworm damage in an onion field.A field trial for testing the effects of different insecticidal treatments on plantdensity, wireworm damage (%) and total onion yield, was conducted at the Institutefor Vegetable Crops (Smederevska Palanka, Serbia) in 2024. The experiment consistedof six treatments: an untreated control, three natural insecticides (two formulationsof spinosad a.i. - granular and liquid, and Beauveria bassiana ATCC 74040 2.3×107conidiospores/ml), a semi-synthetic insecticide (a.i. spinetoram) and a syntheticinsecticide (a.i. tefluthrin). The insecticides were applied during planting, followingtheir label application rates per hectare. Assessments were conducted 20 and 42 daysafter treatment (DAT) to determine plant density. Wireworm damage was specificallyevaluated 42 DAT, and yield was calculated by weighing the harvested onion bulbs. Theresults showed that the granular spinosad formulation, applied in furrows at planting,significantly increased plant density 20 DAT, while its liquid formulation, applied asa soil treatment during planting, resulted in the lowest density. Spinetoram showedthe highest plant density 42 DAT and the highest percentage of wireworm damage(15%) of all insecticides tested. The control had the highest percentage of damagedplants and the lowest yield. Onion yield was at the maximum after treatment withspinetoram, whereas the lowest yield was achieved after treatment with the granularspinosad formulation.Field trials show that natural and semi-synthetic insecticides can effectivelycontrol wireworms, ensuring adequate crop protection and viable yields. Thisstudy supports developing and adopting environmentally conscious soil pestmanagement.
Keywords: Elateridae; biopesticides; insecticides; pest control; yield; onion